2021
DOI: 10.1039/d0tc05736c
|View full text |Cite
|
Sign up to set email alerts
|

Long lifetime phosphorescence and X-ray scintillation of chlorobismuthate hybrids incorporating ionic liquid cations

Abstract: Phosphorescence and X-ray scintillation are achieved for chlorobismuthate hybrids incorporating ionic liquid cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…In addition, other organic constituents, including chiral dications, [ 54 ] aromatic carboxyl anions, [ 55 ] and ionic liquid cations, [ 56 ] were introduced into the inorganic metal halide skeleton to produce hybrid OIMHs with RTP. For example, Du and coworkers used two organic acids, terephthalic acid (TPA) and 1, 4‐phenylenediacetic acid (PLA), to react with PbBr 2 in alkaline NaOH aqueous solution to form two hybrid OIMHs (TPAPbBr and PLAPbBr, respectively) with organic and inorganic components linked by chemical bonds ( Figure ).…”
Section: Organic–inorganic Metal Halidesmentioning
confidence: 99%
“…In addition, other organic constituents, including chiral dications, [ 54 ] aromatic carboxyl anions, [ 55 ] and ionic liquid cations, [ 56 ] were introduced into the inorganic metal halide skeleton to produce hybrid OIMHs with RTP. For example, Du and coworkers used two organic acids, terephthalic acid (TPA) and 1, 4‐phenylenediacetic acid (PLA), to react with PbBr 2 in alkaline NaOH aqueous solution to form two hybrid OIMHs (TPAPbBr and PLAPbBr, respectively) with organic and inorganic components linked by chemical bonds ( Figure ).…”
Section: Organic–inorganic Metal Halidesmentioning
confidence: 99%
“…Ionic liquid hybrid metal halides (ILMHs), constructed by the combination of various halometalate anions and ionic liquid cations,h ave received high attention in recent years due to their excellent photophysical properties and good processibility. [8][9][10][11][12] More importantly,t he flexible ionic liquid cation and abundant supramolecular interactions endow ILMHs multiple stable states with lower energy barrier, which is favorable for the SCSC transition accompanied by luminescence switching. [9] In 2019, our group reported the thermal-and moisture-induced SCSC transition between [Bzmim] 3 SbCl 6 and [Bzmim] 2 SbCl 5 @IL (Bzmim = 1-benzyl-3-methylimidazoli-um, IL = ionic liquid of [Bzmim]Cl) with triple-mode reversible luminescence switching for potential application in laser-printable rewritable luminescent paper.…”
Section: Introductionmentioning
confidence: 99%
“…ILCs couple either with halometal [18][19][20] or hybrid organic inorganic perovskites (HOIPs) [12,21,22]. The presence of ILCs influences the packing density in the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the ILCs structure will become an important consideration for applications as mentioned earlier. For example, Jin et al have shown that using ILCs with a longer alkyl chain length will result in a lower packing density and decrease the phosphorescence quantum yield [22]. The presence of ionic liquids can also induce the photoluminescence switching phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation